Legal Challenges in Technology Development Artificial Intelligence (AI) - Prawitasari, Nining Yurista (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 5 (2025): The 8th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2025)
The development of Artificial Intelligence (AI) technologies has created significant changes in various spheres of human life. However, this rapid progress brings with it complex legal challenges. This research aims to identify, analyze, and offer solutions to legal problems that arise along with the development of AI. The main focus includes aspects of privacy, ethics, security and responsibility. Through this study, there is an in-depth explanation of the latest legal updates, efforts to regulate, as well as suggestions to overcome these problems. In doing so, this research contributes to a deeper understanding of the legal dynamics associated with the development of AI technologies and encourages further discussion in this field.